Transmission Electron Microscopy and Dynamic Light Scattering-Fundamental Perspective (Cognition, 2024)
Transmission Electron Microscopy (TEM) and Dynamic Light Scattering (DLS) are fundamental tools in nanotechnology and materials science, providing information about the structural and dynamic properties of nanomaterials and colloidal systems. This review provides a thorough examination of TEM and DLS, beginning with a discussion of their fundamental principles. It discusses the interaction of electron beams in TEM and the dynamics of scattered light in DLS, followed by an examination of instrumentation and experimental setups, including recent advances for increased resolution and sensitivity. The article then discusses the numerous applications of TEM and DLS in nanomaterial characterization. It includes analyses of nanoparticle size, shape, morphology, and distribution, as well as research into colloidal system dynamics such as nanoparticle aggregation, diffusion, and stability. The review concludes with a forward-looking perspective on emerging trends and future directions in nanomaterial characterization. It emphasizes the potential of TEM and DLS to overcome current challenges and advance our understanding of nanoscale phenomena. Overall, this comprehensive review provides researchers and practitioners with a solid understanding of the TEM and DLS principles, methodologies, and applications, as well as valuable fundamental insights.